Dental caries prevalence, tooth brushing and periodontal status in 150 young people in Istanbul: A pilot study - (:unkn) unknown (WILEY, 2001)
Objective: To evaluate periodontal conditions, prevalence and determination of dental caries and oral health behaviours in a group of young people in Istanbul. Design: Subjects were orally examined and questioned. Setting: A high school in Istanbul. Subjects: One hundred of fifty students. Results: This study showed that 28 per cent of teenagers had adequate oral hygiene. These findings suggest that 72 per cent of the subjects needed oral hygiene education and required restorative dental care. Conclusions: The present study showed that dental treatment need is very high in the sample group. Strong co-operation should be set up between families, schools, communities, regulators and legislators in order to develop and implement comprehensive oral health promotion programmes.
Keywords: oral hygiene; periodontal disease; dental caries; SURVEY ZIMBABWE 1995; COMMUNITY; DISEASES